Water-soluble jack-knife prawn extract inhibits 5-hydroxytryptamine-induced vasoconstriction and platelet aggregation in humans. Issue 2 (2nd December 2014) - Gamoh, Shuji; Kanai, Tasuku; Tanaka-Totoribe, Naoko; Ohkura, Masamichi; Kuwabara, Masachika; Nakamura, Eisaku; Yokota, Atsuko; Yamasaki, Tetsuo; Watanabe, Akiko; Hayashi, Masahiro; Fujimoto, Shouichi; Yamamoto, Ryuichi
Abstract : Coronary artery spasm plays an important role in the pathogenesis of various ischemic heart diseases or serious arrhythmia. Abstract : Coronary artery spasm plays an important role in the pathogenesis of various ischemic heart diseases or serious arrhythmia. The aim of this study is to look for functional foods which have physiologically active substances preventing 5-hydroxytryptamine (5-HT)-related vasospastic diseases including peri- and postoperative ischemic complications of coronary artery bypass grafting (CABG) from ocean resources in Japanese coastal waters. First, we evaluated the effect of water-soluble ocean resource extracts on the response to 5-HT in HEK293 cells which have forcibly expressed cyan fluorescent protein-fused 5-HT2A receptors (5-HT2A -CFP). Among 5 different water-soluble extracts of ocean resources, the crude water-soluble jack-knife prawn extract (WJPE) significantly reduced maximal Ca 2+ influx induced by 0.1 μM 5-HT in a concentration-dependent manner. The Crude WJPE significantly inhibited, in a concentration-dependent manner, 5-HT-induced constriction of human saphenous vein. 5-HT released from activated platelets plays a crucial roles in the constriction of coronary artery. Next the WJPE was purified for applying the experiment of 5-HT-induced human platelet aggregation. The purified WJPE significantly inhibited 5-HT-induced human platelet aggregation also in a concentration-dependent manner. Based on our findings, jack-knife prawn could be one of a functional food with health-promoting benefits for most people with vasospastic diseases including patients who have gone CABG.